(untitled) (Bangladesh Journal of Medical Science, 2014)
A 19 year-old Bangladeshi female presented with a severe Class II division 1 incisor relation-ship on a Skeletal II base and localized spacing in the upper arch. The lower arch was well aligned. Treatment was commenced using fixed appliances and followed by anterior retraction. This case illustrates the versatility of the fixed appliances in the treatment of those cases exhibiting Class II division 1 malocclusion with spacing. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19158 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.350-352